Design and Simulation of a Sustainable Photovoltaic Electric Plug-In Boat. - Cancela, Ángeles; Lastra, René; Suárez, Víctor; Sánchez, Ángel (European Journal of Sustainable Development, 2016)
The increase of energy prices and environmental catastrophes lead to a development of alternative and renewable energy systems. In this case transport. A high efficient electric engine with a variety of the source replaces the so far used internal combustion engine (ICE). A battery system with a renewable energy provider, like photovoltaic panels, affects promising results. In the last few years the implementation of renewable energy sources, for example photovoltaic and wind energy in Hybrid Renewable Energy Systems (HRES) is becoming more popular. Those systems are very depending on seasonal impacts and that is the main disadvantage. The vehicles, which may be suitable, drive either on land or on water. On water the weight only plays an important role for small sail ships. But the energy consumption increases during the navigation with sail. For those types of systems, which mix many power sources, mathematical simulation has become an object of study for electric battery vehicles and all kind of hybrid configurations and even specific software has been developed. However, there is almost no information about battery electric ship simulations and even less about renewable energy sources applied in these kinds of vehicles. In this paper, a conceptual zero emission electric sailboat is created and simulated. Renewable solar energy and energy storage with batteries, in this case the charging energy is provided by the grid, is implemented. Subsequently independent modular models for each energy system will be development in Matlab®/Simulink® and embedded. All of these simulations are managed by a logic controller implemented in Matlab® as well. Keywords: Simulation, Plug-In Hybrid boat, Renewable Energy.